IMPROVING STUDENTS' LEARNING OUTCOME AND MATHEMATICAL ACTIVITIES THROUGH INQUIRY LEARNING STRATEGY IN CLASS XII IPA-2 SMAN 2 BAGAN SINEMBAH 2014/2015 ACADEMIC YEAR - Yamin, M. (Prodi Teknologi Pendidikan, 2016)
Abstract, The purpose of this study is to examine the improvement of students' learning outcome using inquiry learning strategy and to find out the increase of mathematics learning activities using inquiry learning strategy. This study is an action research which was held at SMAN 2 Bagan Sinembah. The subject is students of Class XII IPA-2 in the academic year 2014/2015 which consists of 40 people, 11 male students and 29 female students. This study was conducted in two cycles, each consists of three meetings. A test was conducted at the beginning and at the end of each cycle in order to see students' mathematical communication ability. The results of cycle I showed that students' average score was 72.7 with 25 students complete and 15 students incomplete and the classical completeness was 62.5%. In the second cycle, the average score was 82.65 with 37 students complete and 3 students incomplete and the classical completeness was 92.5%. There was an increase of 9.5 points on students' learning outcome and hence it can be concluded that inquiry learning strategy leads students' activities to be in good category.Keywords: learning outcome, students' mathematical activities, inquiry learning strategy Abstrak, Tujuan dari penelitian ini adalah untuk mengetahui peningkatan hasil belajar dan peningkatan aktivitas proses pembelajaran matematika siswa dengan menggunakan strategi pembelajaran inkuiri. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan di SMA Negeri 2 Bagan Sinembah Kecamatan Bagan Sinembah. Subjek penelitian adalah siswa kelas XII IPA-2 tahun pelajaran 2014/2015 sebanyak 40 orang yang terdiri dari 11 orang laki-laki dan 29 orang perempuan. Penelitian ini terdiri dari 2 siklus yaitu siklus I terdiri dari 3 pertemuan dan siklus II terdiri dari 3 pertemuan. Tes kemampuan matematika siswa dilakukan di awal dan akhir setiap siklus. Adapun hasil dari penelitian ini dapat dilihat dari: (1) Hasil tes ulangan kemampuan matematika siswa siklus I diketahui nilai rata-rata 72,75, tuntas 25 orang, tidak tuntas 15 orang, ketuntasan klasikal 62,5%; (2) Hasil tes ulangan kemampuan matematika siswa siklus II diketahui nilai rata-rata 82,65, tuntas 37 orang, tidak tuntas 3 orang, ketuntasan klasikal 92,5%, dan peningkatan hasil belajar matematika siswa naik 9,5 poin; (3) Pembelajaran dengan menggunakan strategi pembelajaran inkuiri membuat aktivitas siswa berkategori baik dalam pembelajaran. Kata Kunci : Hasil Belajar, Aktivitas Matematika Siswa, Strategi Pembelajaran Inkuiri.